Polyaniline/activated carbon/copper ferrite (PANI/AC/CuF) based ternary composite as an efficient electrode material for supercapacitor - Pandey V.K.; Verma S.; Verma B. (My University, 2025)
The present study addressed the applicability of waste coconut shells to prepare activated carbon (AC) employing pyrolysis. The obtained AC was then used to prepare a ternary hybrid composite with polyaniline (PANI) and copper ferrite (CuF) through oxidative polymerization. The fabricated electrode exhibited a maximum two-electrode specific capacitance of 248.3 Fg−1, a maximum energy density of 49.66 Whkg−1 (1 Ag−1), and a maximum power density of 5996.6 Wkg−1 (20 Ag−1). Outstanding capacitance retention of 92.8% over 2500 cycles depicted excellent cycle stability. The synthesized supercapacitor electrode material may help develop new generation energy storage devices. © 2022